PERAN RECEIVING DALAM MENINGKATKAN EFISIENSI PENGELOLAAN BARANG MASUK DI HARRIS HOTEL & CONVENTIONS GUBENG SURABAYA - Wicaksono, Rahardian Nugroho; Yuliati, Anik (Program Studi Akuntansi Universitas Flores, 2026)
The management of incoming goods is a crucial aspect of sustainable hotel operations, directly impacting service continuity and operational efficiency. This study aims to analyze the role of the Receiving Department in improving the efficiency of incoming goods management at HARRIS Hotel & Conventions Gubeng Surabaya. A descriptive qualitative method was applied, using observation, interviews, and documentation as the primary data sources. The findings reveal that the implementation of the integrated Visual Hotel Program (VHP) system enhances data accuracy, expedites goods verification, and improves interdepartmental transparency. Additionally, supporting documents such as the Purchase Order (PO) and Daily Market List (DML) play a significant role in preventing discrepancies in received goods. The study also highlights the importance of interdepartmental coordination and the competency of receiving staff in strengthening internal control. With a structured system and procedures in place, the receiving process not only supports daily operations but also ensures the accuracy of financial reports and the overall quality of hotel services.